High density lipoprotein (HDL) reduces renal ischemia/reperfusion injury - Thiemermann, C (2015)
High-density lipoproteins (HDL) have been shown to reduce organ injury and mortality in animal models of shock via modulation of the expression of adhesion molecules and pro-inflammatory enzymes. As renal inflammation plays an important role in the development of ischemia/reperfusion (I/R) injury of the kidney, the aim of this study was to investigate the ability of HDL to alleviate renal dysfunction and injury in a rat model of renal I/R. HDL (80 mg/kg, intravenous) was administered to male Wistar rats 30 min before bilateral renal ischemia for 45 min followed by reperfusion for up to 48 h. After 6-h reperfusion, HDL significantly reduced (1) renal and tubular dysfunction, (2) tubular and reperfusion-injury, and (3) histologic evidence of renal injury. HDL also improved renal function (after 24-h and 48-h reperfusion) and reduced histologic signs of renal injury (after 48-h reperfusion). Administration of HDL significantly reduced the numbers of polymorphonuclear leukocytes (PMN) infiltrating into renal tissues during reperfusion, which was reflected by an attenuation of the increase in renal myeloperoxidase activity caused by I/R. Furthermore, HDL markedly reduced expression of the adhesion molecules, intercellular adhesion molecule-1 (ICAM-1), and P-selectin during reperfusion. The increase in renal malondialdehyde levels caused by renal I/R was also significantly reduced by HDL, suggesting attenuation of lipid peroxidation subsequent to oxidative stress. These results demonstrate that HDL significantly reduces renal I/R injury and severity of ischemic acute renal failure. It is proposed that the mechanism of protection involves reduction of the expression of adhesion molecules, resulting in reduction of PMN infiltration and oxidative stress.